Effects of compost-based soil amendments on soil water availability and turmeric yield in sandy and shallow soils of Northeast Thailand - Chomun, Pranee; Thaithet, Sujitra; Khunthong, Sutdacha; Inboonchuay, Tawatchai (Brawijaya University, 2026)
Soil water limitation remains a major constraint on turmeric production in the sandy and shallow soils of northeastern Thailand. This study evaluated the effects of compost combined with selected soil amendments on soil moisture, physical properties, and turmeric yield under rainfed conditions. A three-year field experiment (2021-2023) was conducted using a randomized complete block design with six treatments: control (no compost), compost alone (12.5 t ha-1), and compost combined with biochar (6.25 t ha-1), rice husk ash (6.25 t ha-1), perlite (0.625 t ha-1), and gypsum (1.25 t ha-1). Trials were carried out on sandy and shallow soils in Nakhon Ratchasima Province, Thailand. Amendments generally reduced bulk density and increased saturated hydraulic conductivity compared with the control. Soil moisture and available water capacity (AWC) improved significantly in both soils. Compost combined with rice husk ash resulted in the highest AWC, reaching 13.39% and 9.12% (v/v) in sandy and shallow soils, respectively, and produced the highest fresh rhizome yields (12.72 and 32.83 t ha-1, respectively). Enhanced soil water availability and improved soil structure were strongly associated with increased productivity. Compost alone was less effective under soils with pronounced physical constraints. In contrast, compost combined with rice husk ash consistently outperformed other treatments, indicating a practical strategy to enhance soil water retention, improve physical quality, and increase turmeric yield under rainfed conditions, thereby supporting more sustainable production systems.